(untitled) - Lajtha, Edgar (New York, 1936)
Contents: Part 1. The island and the people. Part 2. The music of the conquerors. Part 3. Working Japan. Part 4. The march on Asia. Part 5. The spirit
Keywords: Japan,Nhật Bản; Description and travel,Mô tả và du hành